Der „critical view of safety“ zur Vermeidung von Gallengangskomplikationen bei der laparoskopischen Cholezystektomie - Grass, Katharina; Oeckl, Karin; Kersting, Stephan (Zentralblatt für Chirurgie, 2020)
Laparoscopic cholecystectomy is one of the most frequently performed procedures worldwide. Therefore, iatrogenic injury to the choledochal duct, although rare, remains a surgical risk that should not be underestimated. Over the years, various methods have been described to avoid this serious complication, with its high morbidity and even mortality. One of the safest methods to avoid bile duct lesions is to establish the so called "critical view of safety" before cutting any structures. This method shall be demonstrated in this instructional video.
CRIS-Team Scopus Importer:2020-09-04